Plexiform Schwannoma Masquerading as Giant Cell Tumor of Tendon Sheath- A Case Report - Singh, Sharanjit; Pendkur, Ganesh; Baveja, Puneet; Roy, Nilanjan (Annals of Pathology and Laboratory Medicine, 2020)
Plexiform schwannoma is a rare benign variant of Schwann cell tumor characterised by multinodular plexiform growth pattern. Usual location of this tumor includes trunk, head, neck and upper extremities but it may rarely be found in lower extremities. It generally affects young adults with no sex predilection. We report a case of 37 years old male who presented with gradually progressive swelling of right little finger of 28years duration that was diagnosed as giant cell tumor of tendon sheath clinically, radiologically and intraoperatively. Authors wish to discuss the case due to its clinical rarity and diagnostic difficulties due to many common histological mimickers at that site.